Phenomenom Cyber Crime in Indonesia in the Digitalization Era - Ellyona Putri, Kadek Devina; Latbin, Mariano Wawan; Bunga, Gerald Aldytia (Journal of Digital Law and Policy, 2024)
Science and technology are increasingly developing rapidly and advancing, offering various interactions in human life. Information and communication technology continues to develop in the digital era, especially the internet, which has a big influence on people's life patterns. The development of the internet has triggered the emergence of a type of cyber crime which is usually known as Cyber Crime. Various cases of cyber crime (Cyber Crime) have emerged in Indonesia, especially in the banking sector. In the following years until now, in Indonesia there have been many incidents of Cyber Crime, for example computer program piracy, cracking, bank burglary (banking fraud), unauthorized use of other parties' credit cards (carding), pornography, including crimes against domain names (domain names). Cyber Crime could happen because unlimited internet access. Apart from that, computer user negligence is also often the cause of this Cyber Crime. This is something that is often overlooked, namely a weak network security system. In fact, a weak network security system creates a big loophole for people who intend to commit crimes. Currently, what is used as the legal basis for Cyber ??Crime cases in Indonesia isLaw Number 11 of 2008 concerning Information and Electronic Transactions (ITE). The ITE Law consists of 13 chapters and 54 articles which explain in detail the rules for living in cyberspace and the transactions that occur therein. Prohibited acts (cybercrime) are explained in Chapter VII (Articles 27-37)